2016
DOI: 10.2214/ajr.15.15380
|View full text |Cite
|
Sign up to set email alerts
|

Acute Lower Gastrointestinal Bleeding: Temporal Factors Associated With Positive Findings on Catheter Angiography After 99mTc-Labeled RBC Scanning

Abstract: TTP and LT impact the rate of positive CA studies. A TTP threshold of ≤ 9 minutes allows the detection of almost all patients who would benefit from CA for treatment and allows a reduction in unnecessary negative CA studies. The likelihood of positive findings on CA decreases with a delay in the performance of CA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
(14 reference statements)
1
9
0
Order By: Relevance
“…Any benefit of shorter times to angiography could not be examined as only 17% (8/48) were performed in under 90 min 53. Similarly a case series of 120 patients with LGIB undergoing red cell scanning found that delays in performing angiography were associated with a reduced chance of demonstrating extravasation of contrast on the angiogram 52. Embolisation is used to control bleeding in a number of other clinical scenarios, including major trauma, UGIB and post partum haemorrhage.…”
Section: Diagnosismentioning
confidence: 99%
“…Any benefit of shorter times to angiography could not be examined as only 17% (8/48) were performed in under 90 min 53. Similarly a case series of 120 patients with LGIB undergoing red cell scanning found that delays in performing angiography were associated with a reduced chance of demonstrating extravasation of contrast on the angiogram 52. Embolisation is used to control bleeding in a number of other clinical scenarios, including major trauma, UGIB and post partum haemorrhage.…”
Section: Diagnosismentioning
confidence: 99%
“…Several studies have shown that more severe bleeds correlate to positive bleeding on TAI. [11] is study did demonstrate a positive relationship between units of pRBCs in the prior 24 h with successful angiography, Table 3. is finding corroborates several prior studies, which have shown that as bleeding severity increases, demonstrated by a drop in hemoglobin and increasing transfusions, the probability of finding a bleed also increases.…”
Section: Discussionmentioning
confidence: 88%
“…The success rate for identification of active contrast material extravasation at fluoroscopic angiography is variable and depends on many factors, such as the location and rate of bleeding (24)(25)(26). The number of cases of active bleeding detected at fluoroscopic angiography has been shown to decrease with increasing time between RBC scintigraphic detection of bleeding and initiation of the angiographic evaluation (27).…”
Section: Endoscopic Evaluation Of Acute Gi Bleedingmentioning
confidence: 99%
“…CT angiography is widely available, and with appropriate triage, an angiogram may be acquired within a few minutes. Shortening the delay prior to evaluation is important, given that even a massive hemorrhage can start and stop rapidly over time and lengthening the time between the start of known bleeding and the subsequent implementation of radiologic evaluation results in fewer positive-result examinations (27,30).…”
Section: Ct Evaluation Of Acute Gi Bleedingmentioning
confidence: 99%